KELAYAKAN TEKNIS PENGEMBANGAN AGAVE DI LAHAN KERING BERIKLIM KERING Agave Stub Pattern Development in Dry Land, Dry Climate - Budi Santoso; Mohammad Cholid (Perspektif, 2019)
ABSTRAK Pengembangan agave diarahkan pada lahan kering beriklim kering yang cukup luas ketersediaannya. Potensi curah hujan yang terbatas sekitar 1.347,71 mm/tahun masih dapat mendukung pertumbuhan agave. Tujuan dari penulisan tinjauan ini adalah untuk menginformasikan pola rintisan pengembangan agave di lahan kering, iklim kering di Sumbawa Barat, sehingga dapat diekstrapolasikan ke daerah lain yang memiliki kemiripan sumber daya alam, ekosistem dan kondisi sosial. Program pola rintisan pengembangan agave di Sumbawa Barat mengikuti azas plasma dan inti.  Investor nasional sebagai inti dan para petani sebagai pelaku plasma.  Investor berkewajiban membeli serat kering agave pada saat panen dari para petani plasma dengan harga yang disepakati bersama. Selain itu investor menyediakan sarana produksi dan mesin dekortikator dengan sistem bantuan sosial. Benih Agave disediakan oleh Investor. Pola rintisan pengembanan agave di Sumbawa Barat dilaksanakan di Kecamatan Sekongkang, Poto Tano, dan Alas seluas 5.000 ha yang didukung oleh 10.000 Kepala Keluarga (KK). Dalam pelaksanaan pengembangan pola rintisan agave ini didukung dengan penyediaan paket teknologi berupa benih agave dari kultur jaringan; sistem tanam double row dan rapat; pengendalian penyakit; pengendalian gulma; aplikasi Ca dan Mg; dan teknologi pasca panen. Pengembangan agave di daerah rintisan hendaknya secara sosial dapat diterima oleh masyarakat, secara ekonomi menguntungkan dan mempunyai nilai tambah, tidak merusak lingkungan, dapat dikerjakan oleh petani, produk yang dihasilkan memiliki daya saing yang tinggi serta berorientasi dari produk primer ke sekunder. ABSTRACTAgave development is allocated to a dry up land area with dry climate, which is still available in large extent. The low annual rainfall of 1.347,71 mm is potentially sufficient for agave development. The purpose of this review is to provide information of the development of agave pioneer pattern on dry upland with dry climate in West Sumbawa, with the expectation that it can be extrapolated to other areas with similar natural resources, ecosystems and social conditions. The initial agave development program in West Sumbawa is based on nucleus and plasma principles. National investors as a nucleus and farmers as actors of plasma. Investors are obliged to buy a dry fiber agave at the harvesting from the farmers with a mutually agreed price. Additionally, investor provides production facilities, machinery dekorticator and seeds in the form of social assistance system. The pioneer pattern of agave development  in West Sumbawa was carried out in Sekongkang, Poto Tano and Alas districts and covered the areas of 5,000 ha involving 10,000 household (HH). In the implementation of the agave development pattern, it is supported by the provision of technological package consisting of agave seeds derived from tissue culture; densely double row planting system; disease control; weed control, application of Ca and Mg; and post-harvest technology.  Stub pattern agave development in the area should be socially acceptable by society, economically profitable and value-added, do not damage the environment, can be done by farmers, the products have high competitiveness and oriented from primary to secondary products. The development of agave in the pilot area should be socially acceptable to the community, economically profitable and has added value, does not damage the environment, can be done by farmers, the products produced have high competitiveness and are concentrated from primary to secondary products